1992
DOI: 10.1002/jts.2490050212
|View full text |Cite
|
Sign up to set email alerts
|

The impact of combat trauma across the family life cycle: Clinical considerations

Abstract: Clinical erperience and research with veterans of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Indeed, these interpersonal difficulties have been shown to mediate associations between PTSD and marital outcomes among Vietnam veterans (MacDonald et al, 1999). Second, tending to a returned spouse with a chronic emotional problem or a physical disability represents an unexpected caregiving burden, one that the partner may not be prepared to bear (Beckham, Lytle, and Feldman, 1996;Dekel et al, 2005;Scaturo and Hayman, 1992). The results of dealing with the emergent problems of a traumatized partner can be problematic in themselves, a phenomenon known as secondary traumatization (Figley, 1998).…”
Section: Emergent Traitsmentioning
confidence: 99%
“…Indeed, these interpersonal difficulties have been shown to mediate associations between PTSD and marital outcomes among Vietnam veterans (MacDonald et al, 1999). Second, tending to a returned spouse with a chronic emotional problem or a physical disability represents an unexpected caregiving burden, one that the partner may not be prepared to bear (Beckham, Lytle, and Feldman, 1996;Dekel et al, 2005;Scaturo and Hayman, 1992). The results of dealing with the emergent problems of a traumatized partner can be problematic in themselves, a phenomenon known as secondary traumatization (Figley, 1998).…”
Section: Emergent Traitsmentioning
confidence: 99%
“…Research convincingly shows that the effects of war can be detrimental to the physical and psychological well being of veterans and their families (e.g., Griffin & Morgan, 1988;Jordan et al, 1992;Scaturo & Hayman, 1992;Williams, 1980). Participation in combat-related activities affects personality development, patterns of social adjustment, coping styles, and interpersonal functioning (Williams, 1980), and is associated with the development of Posttraumatic Stress Disorder (Carroll, Rueger, Foy, & Donahoe, 1985) and substance abuse (Jordan et al, 1992).…”
mentioning
confidence: 99%
“…As Basham (2008) stated in her research on couple's detachment as related to combat trauma, "traumatized military couples represent a new population for the application of attachment theory concepts" (p. 83). Furthermore, Scaturo and Hayman (1992) have noted the clinical significance in discovering if the combat trauma occurred before or after the beginning of the couple's relationship, as they found that couples who were together before the traumatization occurred were more likely to encounter relational difficulties, because their relationship was previously based on an attachment that did not include PTSD-like symptoms. Couples, however, who met after the traumatization occurred were more likely to be cognizant of these symptoms and as such were less likely to notice changes in attachment (Scaturo & Hayman, 1992).…”
Section: Therapeutic Framework and Related Focused Genogram Questionmentioning
confidence: 96%
“…Couples and families often encounter relational difficulties that are distinctive to military culture, which can be more voluminous when the military service personnel is a woman rather than a man. One of the main pathological issues that military couples sometimes struggle with is the change in attachment before and Downloaded by [University of Colorado -Health Science Library] at 08:05 26 December 2014 after the service member goes off to war, on deployment, or completes a military exercise, which can contribute to PTSD in the service member (Scaturo & Hayman, 1992). Such couples may find that their relationship drastically changes from pre-to post-war deployments and many experience adjustment-related conflict.…”
Section: Downloaded By [University Of Colorado -Health Science Librarmentioning
confidence: 99%